Visual Motion Interferes with Tactile Motion Perception - Craig, James C (Perception (London), 2006)
Previous studies have demonstrated that visual apparent motion can alter the judgment of auditory apparent motion. We investigated the effect of visual apparent motion on judgments of the direction of tactile apparent motion. When visual motion was presented at the same time as, but in a direction opposite to, tactile motion, accuracy in judging the direction of tactile apparent motion was substantially reduced. This reduction in performance is referred to as ‘the congruency effect’. Similar effects were observed when the visual display was placed either near to the tactile display or at some distance from the tactile display (experiment 1). In experiment 2, the relative alignment between the visual and tactile directions of motion was varied. The size of the congruency effect was similar at 0° and 45° alignments but much reduced at a 90° alignment. In experiment 3, subjects made confidence ratings of their judgments of the direction of the tactile motion. The results indicated that the congruency effect was not due to subjects being unsure of the direction of motion and being forced to guess. In experiment 4, static visual stimuli were shown to have no effect on the judgments of direction of the tactile stimuli. The extent to which the congruency effect reflects capture effects and is the result of perceptual versus post-perceptual processes is discussed.